Reserva de carbono mineral y orgánico en los tipos de suelo de la Ciudad Universitaria Zungarococha Loreto, 2024 - Cardenas Rengifo, Giezi (Universidad Nacional de la Amazonía Peruana, 2025)
The main objective of this research was to determine the mineral carbon reserve distributed in the types of mineral soil in the University City of Zungarococha, which allowed for the quantification of organic carbon and total carbon in the soils identified in the studied area. The work carried out based on test pits at representative points in the area allowed the horizons to be described following the methodology of the Soil Survey Manual. In addition, at least three different soil samples were taken for each test pit and analyzed in the soil research laboratory of the Natural Resources Research Center (CIRNA), and the results were recorded in an observation form and subsequently systematized in Excel spreadsheets. The research is descriptive in nature, and the results obtained have made it possible to describe and update the information on Amazonian soils in this area. It is stated that the soils show marked heterogeneity, with textures ranging from sandy to clayey, which influences their drainage, water retention, and carbon storage capacity. The surface horizons exhibit higher organic matter, darker colors, and higher carbon content (up to 2.6%), while the deep horizons have more clay and greater carbon stability but lower organic content. It was concluded that the calculation of total carbon per hectare confirms that more than 50% is concentrated in the surface horizons. It was concluded that the calculation of total carbon per hectare confirms that more than 50% is concentrated in the top 20–30 cm, and that finer soils store significantly more carbon than sandy soils.

La presente investigación tuvo como objetivo principal determinar la reserva de carbono mineral distribuida en los tipos de suelo mineral en la Ciudad Universitaria de Zungarococha, que permitió alcanzar la cuantificación del carbono orgánico y carbono total en los suelos identificados en la zona estudiada. El trabajo realizado a partir de las calicatas en puntos representativos de la zona, permitieron describir los horizontes siguiendo la metodología del Soil Survey Manual, además se tomaron al menos 3 muestras de suelo distintas para cada calicata, que se analizaron en el laboratorio de investigación de suelos del Centro de Investigación de Recursos Naturales (CIRNA), y los resultados se registraron en una ficha de observación sistematizada posteriormente en Hojas de cálculo Excel. La investigación es de tipo Descriptiva, y los resultados obtenidos han permitido describir y actualizar la información de los suelos amazónicos de esta zona; se afirma que los suelos muestran una marcada heterogeneidad, con texturas que van desde arenosas hasta arcillosas, lo que influye en su drenaje, retención de agua y capacidad para almacenar carbono, donde los horizontes superficiales exhiben mayor materia orgánica, colores más oscuros y contenidos más altos de carbono (hasta 2.6 %), mientras que los horizontes profundos poseen más arcilla y mayor estabilidad del carbono, pero menor aporte orgánico. Se concluyó que, el cálculo del carbono total por hectárea confirma que más del 50 % se concentra en los primeros 20–30 cm, y que los suelos más finos almacenan significativamente más carbono que los arenosos.
Keywords: Carbono total; Carbono orgánico del suelo; Tipo de suelos; https://purl.org/pe-repo/ocde/ford#5.07.01